Perbandingan Epistemologi Al-Farabi dan Immanuel Kant Tentang Rasionalitas - Binti Khalimatuzzahro; Irham Multazam (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Rationality is a central theme uniting Islamic and Western philosophical traditions, although the two proceed from different metaphysical frameworks. This paper aims to comparatively examine the epistemology of Al-Farabi (d. 950 CE), known as the "Second Teacher" after Aristotle, and Immanuel Kant (1724–1804), the founder of critical philosophy, regarding the source and limits of human rationality. A qualitative-descriptive library research method with a philosophical comparative approach was used, drawing on primary translated texts and recent scholarship (Abbaszadeh, 2017; Masykur, 2025; P. Müürsepp et al., 2024). The findings show that Al-Farabi views rationality as a graded faculty of the soul that reaches perfection through emanation from the Active Intellect, situating reason within a hierarchical, metaphysically optimistic cosmos in which philosophy and religion converge on the same truth (Suleimenov, 2019; Zeraoui & Gonzalez Uresti, 2021). Kant, conversely, views rationality as the subject's own structuring activity, organizing experience through a priori forms and categories while critically confining theoretical reason to the realm of phenomena, leaving the noumenal realm beyond its reach (Anderson, 2022; Katrechko, 2023). Both place reason as the primary source of certainty not derived solely from sense experience, yet differ fundamentally in their metaphysical orientation: Al-Farabi's emanative-cosmic model versus Kant's critical-transcendental model. This comparison is expected to enrich contemporary Islamic epistemological discourse in dialogue with modern Western philosophy.